PROSES BERPIKIR KRITIS BERDASARKAN GAYA BELAJAR DALAM MEMECAHKAN MASALAH SOAL CERITA MATEMATIKA - Sufyan; Rukli; Agustan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to obtain an overview of students' critical thinking processes in solving mathematical problems based on visual, auditory, and kinesthetic learning styles. The identification of critical thinking processes was guided by the IDEALS steps, namely Identify, Define, Enumerate, Analyze, List, and Self-Correct. The research subjects consisted of three students, each with the highest score in visual, auditory, and kinesthetic learning styles. This study used a qualitative descriptive method with data collected through observation, interviews, documentation, and students' test results. Technical triangulation was employed to validate the data. The results showed that in the steps of identifying, enumerating, analyzing, listing, and self-correcting, the critical thinking processes of visual, auditory, and kinesthetic students had similarities in solving story problems. Differences were most evident in the define step, particularly in how and when students explained the shape of the aquarium based on facts and logical reasoning. Another difference was seen in the accuracy of re-examining answers, with the auditory student adding notes to the response. The kinesthetic student demonstrated a better critical thinking process than the visual student in the define step, while the visual student outperformed the auditory student, who showed doubt about the question.